Modeling amino acid requirements of poultry - Sakomura, Nilva K. [UNESP]; Silva, Edney P. [UNESP]; Dorigam, Juliano C. P. [UNESP]; Gous, Robert M.; St-Pierre, Normand (Oxford Univ Press, 2015)
Poultry nutritionists should constantly evaluate their feeds and feeding programs in view of the changes that continue to be made to the potential growth rate of broilers and egg production in laying hens with the objective of providing the birds with the optimum economic level of nutrients at all times. In this review, the models generated at Universidade Estadual Paulista (UNESP) Jaboticabal, to estimate the optimum intake of amino acids (AA) for broilers and laying hens are presented. These models were used to estimate the variation in AA intake within a broiler population making use of coefficients of variation that represent the real situation in a commercial broiler operation. The range of AA intakes obtained was compared to some commonly applied feeding programs and recommendations. Based on results of our developed models and other feeding programs, feeds were formulated and growth was predicted using a growth simulation model (Avinesp). The prediction of growth showed that these models are reliable and useful tools to assist the nutritionists in decision making. In a study with laying hens, the Reading model (RM) was used to establish optimum economic AA intakes in a flock of hens. The input variables were the means and standard deviations of egg output and BW, and the relationship between the marginal cost of the AA and the marginal revenue for eggs. Based on this model, the optimum intake of each AA can vary with each of the variables considered. The models proposed in our study enable important decisions to be made regarding AA intakes to be used to obtain optimum economic performance from a population of broilers and laying hens.
Keywords: amino acids; broiler; economic; efficiency; laying hens; stochastic model